PROFIL PENGETAHUAN PEKERJA SEKS KOMERSIAL (PSK) TENTANG HIV/AIDS DI DUKUH NGLEBOK KECAMATAN CEPU KABUPATEN BLORA - Zulaika, Chusnul Zulaika Zulai (STIKES Widya Husada Semarang, 2010)
Disease of infection of HIV / AIDS represent the problem of biggest health. Amount of suffered of HIV /AIDS in Indonesia in the year 2006 is 165.000 - 250.000. while in Central Java in the early year 2007 tendingto increase there are 1070 patient of HIV / AIDS consist of 830 patient of HIVDAN 240 patient of AIDS. InBlora during three year partake - partake in District Of Casket Hamlet of Nglebok and in Blora in KampongJust known 17 one who is infection of HIV, altogether PSK which are positive infection of HIV. So that can beformulated by problem